MENTERI HUKUM DAN HAK ASASI MANUSIA SEBAGAI KUASA PERMANEN PRESIDEN DALAM PENGUJIAN UNDANG-UNDANG - Mattalatta, Andi (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
“In the judicial review of the law, the Constitutional Court mayrequest to the President information relating to the applicationbeing trialed. Presidential statement is a government’s officialstatement both orally and in writing on the subject matters as aresult of coordination of the relevant ministers and/orInstitutions/Government Agencies. Considering Presidentactivities either as Head of state or Head of Government, thePresident appoints permanently the Minister of Law and HumanRights and the relevant ministers, and/or minister level officialsas its proxy with substitution right. Because of the position ofthe Minister of Law and Human Rights as the assistant of thePresident in the field of Law and Human Rights, with one ofhis responsibilities in the field of legislation, Minister of Lawand Human Rights is appointed as the permanent proxy by thePresident for the purpose of judicial review of the Constitutionof the Republic of Indonesia Year 1945